Effects of different neuromuscular training modalities on balance performance in older adults: a systematic review and network meta-analysis - Yuanji Zhong; Pengwei Chen; Wenhao Guo; Yongshun Wang; Yang Xue; Penghong Chen; Jingjin Liu (Frontiers in Physiology)
BackgroundNeuromuscular training (NMT) is widely utilized to enhance balance and reduce fall risk in older adults, yet comparative effectiveness across various modalities remains unclear. This study aimed to systematically assess and rank the effects of sensorimotor training (ST), whole-body vibration training (WBVT), neurofunctional training (NT), and balance training (BT) on balance performance in older adults.MethodsA systematic review and network meta-analysis was conducted following PRISMA guidelines, including 49 randomized controlled trials with a total of 3,028 older adults. Intervention efficacy was assessed through dynamic balance (Timed Up and Go Test [TUGT], Walk Test [WT]) and static balance (Berg Balance Scale [BBS]) outcomes.ResultsSignificant improvements in dynamic balance (TUGT) were observed with ST (SMD = −0.92; 95% CI: −1.66, −0.18) and NT (SMD = −0.92; 95% CI: −1.44, −0.40), which ranked highest in efficacy (NT: 85.9%, ST: 83.4%). WBVT (SMD = −0.35; 95% CI: −0.69, −0.02) and BT (SMD = −0.33; 95% CI: −0.64, −0.01) also showed statistically significant, but modest effects on dynamic balance. In contrast, the effects of all interventions on static balance, as measured by the BBS, were not statistically significant, suggesting limited and inconclusive evidence regarding their impact on postural stability. Although ST ranked highest in WT (73.7%) and BT showed a favorable SUCRA value in BBS (60.2%), these rankings should be interpreted with caution.ConclusionThe corresponding effect sizes were small and not statistically significant, indicating that SUCRA reflects relative ranking probability rather than actual clinical efficacy. Therefore, the potential benefits for improving static balance and walking speed remain limited and inconclusive. ST and NT were identified as the most effective NMT modalities for significantly enhancing dynamic balance in older adults, indicating their suitability for targeted interventions in fall prevention strategies.Systematic Review Registrationhttps://inplasy.com/inplasy-2025-4-0015/, identifier INPLASY202540015